1989
DOI: 10.1002/jat.2550090411
|View full text |Cite
|
Sign up to set email alerts
|

The dermal carcinogenic potential of unrefined and hydrotreated lubricating oils

Abstract: Unrefined lubricating oils contain relatively high levels of polycyclic aromatic hydrocarbons (PAH) and have been shown to induce tumors in mouse skin. Exxon has developed a new method of refining these materials, a severe hydrotreatment process that is optimized for PAH removal. The specific objectives of the current study were to assess PAH reduction and then to evaluate directly the dermal carcinogenic potential of the materials that spanned the range of products produced by this method. The test samples in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…For mineral oils, products with a high concentration of polycyclic aromatic compounds (PAC) with 3-7 rings (parent PAHs, short-alkylated MOAH, compounds containing heteroatoms), such as unrefined and poorly refined base oils, were carcinogenic in mouse skin painting assays (Roy et al 1988;McKee, Daughtrey, et al 1989;Blackburn et al 1996;Mackerer et al 2003). The aromatics concentration was determined by target analytics for specific parent PAHs (McKee, Daughtrey, et al 1989;Concawe 1994) and by solvent extraction with dimethyl sulfoxide (DMSO) followed by GC separation according to the ring number using two to seven ring unsubstituted PAHs as internal standards (Roy et al 1988;Mackerer et al 2003;Gray et al 2013). The latter technique is used by the Mobil PAC Method for predicting dermal carcinogenicity (see below).…”
Section: Carcinogenicity Of Pahs and Moahmentioning
confidence: 99%
See 3 more Smart Citations
“…For mineral oils, products with a high concentration of polycyclic aromatic compounds (PAC) with 3-7 rings (parent PAHs, short-alkylated MOAH, compounds containing heteroatoms), such as unrefined and poorly refined base oils, were carcinogenic in mouse skin painting assays (Roy et al 1988;McKee, Daughtrey, et al 1989;Blackburn et al 1996;Mackerer et al 2003). The aromatics concentration was determined by target analytics for specific parent PAHs (McKee, Daughtrey, et al 1989;Concawe 1994) and by solvent extraction with dimethyl sulfoxide (DMSO) followed by GC separation according to the ring number using two to seven ring unsubstituted PAHs as internal standards (Roy et al 1988;Mackerer et al 2003;Gray et al 2013). The latter technique is used by the Mobil PAC Method for predicting dermal carcinogenicity (see below).…”
Section: Carcinogenicity Of Pahs and Moahmentioning
confidence: 99%
“…Test materials were applied undiluted in a defined volume to the shaved backs of the animals 1-3 times per week (Doak et al 1983;Blackburn et al 1984;Doak et al 1985;Blackburn et al 1986;Roy et al 1988;McKee, Daughtrey, et al 1989;McKee, Nicolich, et al 1990;Chasey and McKee 1993;Concawe 1994). In some cases, test materials were diluted in highly refined mineral oil or toluene for reasons of high toxicity or high viscosity (Blackburn et al 1986;McKee, Daughtrey, et al 1989;McKee, Nicolich, et al 1990). Only some studies reported the size of the dermal treatment area (McKee, Daughtrey, et al 1989;Chasey and McKee 1993).…”
Section: Carcinogenicity Of Pahs and Moahmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower carcinogenic activity from biologically active PACs in residual oils compared to distillate oils has been observed in skin-painting assays. 62,63 In addition, residual LOBs can have much lower carcinogenicity than would be expected on the basis of the amount of material extracted by DMSO with the IP346 method 6 , leading CONCAWE (Conservation of Clean Air and Water in Europe) to conclude that the IP346 method is not suitable for substances, such as some residual oils, that contain large PACs (asphaltenes) and/or resins. 7 Analytical studies of these de-asphalted vacuum residua indicate that the aromatics they contain are predominantly 1-3 ring compounds that are highly alkylated (paraffinic and naphthenic).…”
Section: Significance Of Distillate Versus Residual Lobsmentioning
confidence: 99%